Rukn Al-Aʼimmah Abd Al-Kareem Ibn Muhammad Al- Sbaghy and his Jurisprudential Opinions - Saidi, Rafet Ali (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: The study aims to introduce one of the flags of the Hanafi school, which is Rukn al-aʼimmah Sabbaghi, by explaining the personal aspect of his life such as his birth and death, and the definition of his name, lineage and surname, and stand on the scientific side of him by reviewing his elders, students and writings. It follows his jurisprudential sayings broadcast in the books and sources of the Hanafi school. Methods: The study followed the appropriate approaches, which were: Inductive approach: by collecting the scientific material from its contents in the sources and references that the researcher was able to access. The study also followed the deductive analytical approach: by analyzing the scientific material and arranging it to reach the results and conclusions shown on scientific grounds. Results: The study reached a number of results, the most important of which are: Imam Sabbaghi reached the degree of Mujtahid in the Hanafi school, Imam Sabbaghi has a number of books, the most important of which is sharh Al-Qudduri, one of the most important sheikhs of Imam Al-Sabbaghi Abu Al-Yusr Al-Bazdawi, the opinions of Imam Al-Sabbaghi are considered and approved in the Hanafi school. Conclusion: The study concluded that Imam Sabbaghi reached the rank of ijtihad in the Hanafi school, as he is from the class of advanced mujtahids of the doctrine, and the importance of tracking his jurisprudential statements broadcast in the books of the Hanafi school.